Respuestas

2012-10-01T18:51:06+02:00

1.-(x + 9) (x + 4) =x.x+4.x+9.x+9.4=x^{2}+4x+9x+36=x^{2}+11x+36  todos son similares   SUERTE!!!!

2.- (x – 8) (x – 2) =
3.- (x + 6) (x – 1) =
4.- (x – 4) (x + 2) =
5.- (x + m) (x + y) =
6.- (x -1) (x – 2) =
7.- (x – 6) (x – 9) =
8.- (x + 8) (x – 7) =
9.- (x – 10) (x + 8) =
10.- (x – c) (x + d) =

1.-(x + b) (x + a) =
2.- (x +4) (x – 10) =
3.- (x + 6) (x – 1) =
4.- (x – 4) (x + 2) =
5.- (x + m) (x + y) =
6.- (x + 11) (x – 7) =
7.- (x – 2) (x +5) =
8.- (x + 4) (x – 10) =
9.- (x – 1) (x + 5) =
10.- (x – 2) (x + 4) =